Reduced Lysosomal Acid Lipase Activity in Blood and Platelets Is Associated With Nonalcoholic Fatty Liver Disease. Issue 2 (14th February 2020) - Ferri, Flaminia; Mischitelli, Monica; Tozzi, Giulia; Messina, Emanuele; Mignini, Irene; Mazzuca, Sergio; Pellone, Monica; Parisse, Simona; Marrapodi, Ramona; Visentini, Marcella; Baratta, Francesco; Del Ben, Maria; et al.
Abstract : OBJECTIVES: To investigate whether blood total lysosomal acid lipase activity (BT-LAL) levels are uniquely associated with the noncirrhotic and cirrhotic stages of nonalcoholic fatty liver disease (NAFLD) and with protection from NAFLD in metabolically/genetically predisposed subjects and a normal liver. To clarify which enzyme-carrying circulating cells are involved in reduced BT-LAL of NAFLD. METHODS: In a cross-sectional study, BT-LAL was measured by a fluorigenic method in patients with NAFLD (n = 118), alcoholic (n = 116), and hepatitis C virus-related disease (n = 49), in 103 controls with normal liver and in 58 liver transplant recipients. Intracellular platelet and leukocyte LAL was measured in 14 controls and 28 patients with NAFLD. RESULTS: Compared with controls, (i) BT-LAL and LAL in platelets, but not in leukocytes, were progressively reduced in noncirrhotic NAFLD and in nonalcoholic steatohepatitis-related cirrhosis; (ii) platelet and leukocyte counts did not differ in patients with noncirrhotic NAFLD; and (iii) BT-LAL did not differ in alcoholic and hepatitis C virus noncirrhotic patients. BT-LAL progressively increased in controls with metabolic syndrome features according to their PNPLA3 rs738409 steatosis-associated variant status (II vs IM vs MM), and their BT-LAL was higher than that of noncirrhotic NAFLD, only when carriers of the PNPLA3 unfavorable alleles were considered. Liver transplant recipients with de novo NAFLD compared with those without de novo NAFLD had lower BT-LAL. DISCUSSION: LAL in blood and platelets is progressively and uniquely reduced in NAFLD according to disease severity. High BT-LAL is associated with protection from NAFLD occurrence in subjects with metabolic and genetic predisposition. Low LAL in platelets and blood could play a pathogenetic role in NAFLD.